PENYERTAAN MODAL DAN BANTUAN MANAJEMEN OLEH PERUSAHAAN MODAL VENTURA DALAM RANGKA MENGEMBANGKAN PERUSAHAAN PASANGAN USAHA - Dita Widyantari, Made; Bagiastra, I Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 02, Februari 2014, 2014)
Along with the competition in today's business, capital and management are the essential for building and developing a business. Financing through venture capital can be a solution for a company, because equity investment and relief operations management are carried out by a venture capital company as a form of responsibility by venture capital company in order to develop the business of the investee company. Thus, it can be drawn a conclusion that the venture capital company in helping the investee company not only in the form of equity investment but also helping the management in order to develop the investee company on their maximum competences. In writing this paper the authors use this type of normative legal research.
Keywords: equity investment, management, venture capital